The Sultan's communists Moroccan Jews and the politics of belonging - Heckman, Alma Rachel (Stanford, California Stanford University Press, 2020)
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- NOTE ON TRANSLATION AND TRANSLITERATION -- FREQUENTLY USED ABBREVIATIONS -- THE SULTAN’S COMMUNISTS: AN INTRODUCTION -- CHAPTER 1 CHOICES: FASCISM AND ANTI-FASCISM IN INTERWAR MOROCCO -- CHAPTER 2 POSSIBILITIES: WORLD WAR II AND MOROCCAN JEWISH BELONGING -- CHAPTER 3 TACTICS: JEWS AND MOROCCAN INDEPENDENCE -- CHAPTER 4 SPLINTERS: DISILLUSION AND JEWISH POLITICAL LIFE IN THE NEW MOROCCO -- CHAPTER 5 CO-OPTATION: THE MOROCCAN COLD WAR, ISRAEL, AND HUMAN RIGHTS -- SCARIFICATION: A CONCLUSION -- NOTES -- BIBLIOGRAPHY -- INDEX
The Sultan's Communists uncovers the history of Jewish radical involvement in Morocco's national liberation project and examines how Moroccan Jews envisioned themselves participating as citizens in a newly-independent Morocco. Closely following the lives of five prominent Moroccan Jewish Communists (Léon René Sultan, Edmond Amran El Maleh, Abraham Serfaty, Simon Lévy, and Sion Assidon), Alma Rachel Heckman describes how Moroccan Communist Jews fit within the story of mass Jewish exodus from Morocco in the 1950s and '60s, and how they survived oppressive post-independence authoritarian rule under the Moroccan monarchy to ultimately become heroic emblems of state-sponsored Muslim-Jewish tolerance. The figures at the center of Heckman's narrative stood at the intersection of colonialism, Arab nationalism, and Zionism. Their stories unfolded in a country that, upon independence from France and Spain in 1956, allied itself with the United States (and, more quietly, Israel) during the Cold War, while attempting to claim a place for itself within the fraught politics of the post-independence Arab world. The Sultan's Communists contributes to the growing literature on Jews in the modern Middle East and provides a new history of twentieth-century Jewish Morocco
Archivierung/Langzeitarchivierung gewährleistet
Keywords: JEWISH communists -- Morocco -- History -- 20th century; Jews -- Morocco -- Politics and government -- 20th century; Nationalism and communism -- Morocco -- History -- 20th century; History / Jewish